The practical encyclopedia of martial arts - Goodman, Fay (Lorenz Books, 2004)
Offers advice on choosing the best discipline for men and women of all ages and fitness levels, for children and for people with disabilities. Annotation. Offers advice on choosing the best discipline for men and women of all ages and fitness levels, for children and for people with disabilities.